Wild Fruits with Respect to Food and Nutrition in Karnataka, India - Sarala P; Krishnamurthy S.R (International Journal of Pharma and Bio Sciences, 2022)
: An attempt has been made to document wild fruits concerning food value and nutrition in different regions of Karnataka. The 45 different wild fruits are documented on the basis of interviewing the local people for uses, medicinal value and preparation of value-added products. The fruits showed variation regarding morphology, juice yield, powder yield, proximate and nutritive value, and elemental components. The comparative study with RDA value confirms the food supplements properties of wild fruits. The uses of fruits in particular and other parts, in general, differ from region to region. The fruits are not only sources of nutrient supplements but also one of the essential resources for income generation at middle regions of Western Ghats. Further, raw and processed products are essential traditional ingredients for preparing local dishes. Among the different regions, the fruits are harvested, processed, and used based on traditional methods and knowledge. The study confirmed that the conservation of wild fruits needs both in vitro and in vivo approaches. The awareness among the local people, encouragement from government organization, voluntary involvement of NGO and involvement of local people and women for biodiversity conservation helped to develop the potential of wild fruits for farmers/collectors to market. The present study initiates the utilization of wild fruits for better uses and to establish plant-based cottage industries to provide employment and generate income by the rural people of Western Ghats of Karnataka.